WILD ANIMAL CONTENT MONETIZATION ON YOUTUBE: A LITERATURE STUDY - Altamira, Melisa Bunga; Permana Putri, Khairunnisa Devani Aqtus; Tata Samudra, Raden Muhammad Rafi; Yuliafni, Fildza Astri (UI Scholars Hub, 2022)
Today's social media is used for various needs. Its nature is easily accessible and can penetrate space and time, making social media the main platform for sharing information or even selling products. Along with the massive use of social media, currently, users can not only use social media as an information-sharing platform but can also monetize their accounts through a variety of content that is presented. In recent years, the world of social media, especially YouTube, has been quite busy with content owned by monetized wildlife by public figures and celebrities. Wild animals are defined as animals or animals that live in the wild without human intervention. Monetization of wildlife content has the potential to persuade audiences to do the same. This study highlights the phenomenon of monetization of wildlife through content on social media, especially YouTube, which is rife in Indonesia. Through a qualitative study of literature and observation, this study will present information related to the monetization of wildlife through social media content in Indonesia and its impact on the sustainability and welfare of wildlife in Indonesia.